The last song [compact disc, unabridged] - Sparks, Nicholas (Hachette Audio, 2009)
Seventeen-year old Veronica "Ronnie" Miller's life was turned upside down when her parents divorced and her father moved to Wrightsville Beach, North Carolina. Three years later, when she and her younger brother are sent to spend the summer with her father, she remains angry and alienated from her parents. Ronnie finds herself falling in love, opening herself up to the greatest happiness - and pain -that she has ever known.